ANALISIS KEPUASAN MASYARAKAT DALAM MENINGKATKAN KUALITAS PENYELENGGARAAN PELAYANAN PUBLIK (STUDI KASUS UPT RUMAH SAKIT KHUSUS MATA) PRIVINSI SUMATERA UTARA - Rahima Purba (Journal of Economic and Business, 2022)
This research is entitled "Analysis of Community Goals in Improving the Quality of Public Service Delivery". This research on accountability was conducted using qualitative research methods. Data collection techniques in this study were in the form of observation, interviews, and documentation. primary and secondary data This study uses IKM data techniques in accordance with KEPMENPAN Number 25 of 2004 concerning General Guidelines for Compiling the Community Index of Government Service Unit Service Units. Based on the 14 elements of service that must be achieved, politeness and the lowest level is the IKM value of 76.00 and is at a good level. cost guarantee with an IKM value of 70.00 and is at a less good level.